Monocyte implication in renal allograft dysfunction. (February 2014) - Guillén‐Gómez, E.; Guirado, L.; Belmonte, X.; Maderuelo, A.; Santín, S.; Juarez, C.; Ars, E.; Facundo, C.; Ballarín, J. A.; Vidal, S.; Díaz‐Encarnación, M. M.
Summary Macrophages are involved in the development and progression of kidney fibrosis. The aim of this study was to analyse the phenotype of circulating monocytes and their ability to predict kidney allograft dysfunction in living kidney transplant recipients. Whole blood samples from 25 kidney recipients and 17 donors were collected at five time‐points. Monocyte phenotype was analysed by flow cytometry, and interleukin (IL)‐10 and soluble CD163 by enzyme‐linked immunosorbent assay. One week after transplantation, surface CD163 and IL‐10 levels increased significantly from baseline [2·99 ± 1·38 mean fluorescence intensity (MFI) to 5·18 ± 2·42 MFI for CD163; 4·5 ± 1·46 pg/ml to 6·7 ± 2·5 pg/ml for IL‐10]. This CD163 increase correlated with 4‐month creatinine levels (r = 0·4394, P = 0·04). However, soluble CD163 decreased significantly from baseline at 1 week (797·11 ± 340·45 ng/ml to 576·50 ± 293·60 ng/ml). CD14+CD16– monocytes increased at 4 months and correlated positively with creatinine levels at 12 and 24 months (r = 0·6348, P = 0·002 and r = 0·467, P = 0·028, respectively) and negatively with Modification of Diet in Renal Disease (MDRD) at 12 months (r = 0·6056, P = 0·003). At 4 months, IL‐10 decreased significantly (P = 0·008) and correlated positively with creatinine at 2 years (r = 0·68, P = 0·010) and with CD14+CD16– monocytes at 4 months (r = 0·732, P = 0·004). At 24 h, levels of human leucocyte antigen D‐related declined from 12·12 ± 5·99 to 5·21 ± 3·84 and CD86 expression decreased from 2·76 ± 1·08 to 1·87 ± 0·95. Both markers recovered progressively until 12 months, when they decreased again. These results indicate that monitoring monocytes could be a promising new prognostic tool of graft dysfunction in renal transplant patients.